Data curation profiles directory ([Purdue University Libraries], 2009)
A resource for Library and Information Science professionals, Archivists, IT professionals, Data Managers, and others who want information about the specific data generated and used in research areas and sub-disciplines that may be published, shared, and preserved for re-use. Data Curation Profiles capture requirements for a specific data set generated by a single scientist or lab, based on their reported needs and preferences for the data. The purpose of the Data Curation Profiles (DCP) Directory is to enable authors of completed DCPS to publish their work in ways that recognize the scholarship of crafting a DCP, and support the discovery, access and use of DCPs. As they are born-digital, the site also makes a strong commitment to the preservation of DCPs. Metadata records for the Profiles are delivered regularly to the following library discovery tools: Worldcat, Primo, Summon, EBSCO Discovery. Profiles are further indexed by Google Scholar, EBSCO, and ProQuest products.